Doubt and Suspicion among the Deaf and Its Relationship to Social Skills - Al-Masa'deh, Mu'tasem M.; Takash, Hanan M.; Al- Hassan, Omayya M. (Journal of Ecohumanism, 2024)
This study aimed to explore the relationship between feelings of doubt and suspicion among deaf students in deaf schools in Zarqa city and how these feelings affect their social skills. It also aimed to understand the extent to which these feelings affect students' ability to communicate and interact socially and to determine the prevalence of this phenomenon among deaf students. The study sample comprised 45 deaf children from deaf schools in Zarqa city, aged 12 to 18 years. The pupils were randomly chosen from Al Amal School for Deaf Education in the city to guarantee diverse representation within the sample. The researchers used the Doubt and Skepticism Questionnaire and the Social Skills Questionnaire. In this respect, there is a strong negative relationship between doubt and suspicion and the social skills of deaf students; for example, the correlation coefficient is -0.68 (p= 0.01), which states that for any unit increase in the level of doubt and suspicion, social skills decrease. Where the mean score was 4.2 for those students whose level of doubt and suspicion was low, the mean score is 2.8 for those with high levels of doubt and suspicion. A high level of doubt and suspicion was expressed by 35%, and a moderate level by 45%. The effect of age on levels of doubt and suspicion was significant at p = 0.02, with a higher mean score across the older students: 4.0 for those aged between 16 and 18 years and 3.1 among the younger age group. The communication effectiveness also decreased when the levels of doubt and suspicion were higher: the students scored 4.3 at low levels and 2.9 at high levels.